PENGEMBANGAN PROTOTIPE APLIKASI MEMBUKA KUNCI PINTU OTOMATIS MENGGUNAKAN METODE SIDIK JARI BERBASIS NODEMCU - Fahrur Hady; Muhamamd Sholeh; Dina Andayati (LPPM Universitas Widya Dharma, 2022)
In the current digitalization era, the use of household appliances has been developed using information technology such as the process of using devices using passwords, cards, fingerprints and the like. Likewise, the process of opening doors which is done manually, in the era of digitization can also be developed based on information technology. In this study, a prototype application was developed that could open the door device automatically using a smartphone. The research methodology is carried out by studying literature as a reference for research to be made, observations on software and hardware as well as simulation of hardware and software. The software made in the form of an android application that can detect fingerprints to be able to log into the system and the process of storing usage records with firebase. The hardware uses NodeMCU as a microcontroller board, relay as a current regulator which will be forwarded to the door lock solenoid. The result of the research is an application prototype that can open the door automatically. The process of using the application is done by first logging in using a fingerprint. The application can send commands to open and lock the door automatically. The microcontroller device can realize the command to open and lock the door by activating the solenoid door lock which is set through the NodeMCU and is connected wirelessly via the internet network. Applications can also log all application usage activities. All application usage records are stored in a database. Authority processes in application usage are divided into admin level and user level. At the admin level, admins can view system usage records as well as add, view, modify and delete user data. At the user level, the application is limited to only sending commands in the form of opening and locking doors.